mPer1 and mPer2 mutant mice show regular spatial and contextual learning in standardized tests for hippocampus-dependent learning - Züger, Maha; Urani, A.; Chourbaji, Sabine; Zacher, Christiane; Lipp, Hans-Peter; Albrecht, U.; Spanagel, Rainer; Wolfer, David Paul; Gass, Peter (Journal of neural transmission, 2006)
Learning and memory, like most physiological processes, seem to be under the control of circadian rhythm. The recently cloned mPer1 and mPer2 genes play an important role in the regulation of the circadian rhythm. In this study, we tested mPer1 and mPer2 mutant mice in two different learning and memory paradigms, a water-maze place navigation task and contextual fear conditioning. In both learning tests, the hippocampus is critically involved. None of these learning types were affected by the mutations, suggesting that mPer1 and mPer2 do not play a major role in the regulation of hippocampus-dependent learning and memory.
Published online June 15, 2005
Gesehen am 22.10.2020